2018
DOI: 10.1038/s41598-018-19888-9
|View full text |Cite
|
Sign up to set email alerts
|

Variability in phase and amplitude of diurnal rhythms is related to variation of mood in bipolar and borderline personality disorder

Abstract: Variable mood is an important feature of psychiatric disorders. However, its measurement and relationship to objective measureas of physiology and behaviour have rarely been studied. Smart-phones facilitate continuous personalized prospective monitoring of subjective experience and behavioural and physiological signals can be measured through wearable devices. Such passive data streams allow novel estimates of diurnal variability. Phase and amplitude of diurnal rhythms were quantified using new techniques that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…By contrast, there is very little overlap between healthy control and borderline personality disorder group membership. This finding broadly aligns with other subjective measures of mental state, sampled much more frequently than weekly, which show a gradient of abnormal mood where healthy control<bipolar disorder<borderline personality disorder [ 19 , 20 ]. How more frequent sampling would combine with geolocation data is an important future question.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…By contrast, there is very little overlap between healthy control and borderline personality disorder group membership. This finding broadly aligns with other subjective measures of mental state, sampled much more frequently than weekly, which show a gradient of abnormal mood where healthy control<bipolar disorder<borderline personality disorder [ 19 , 20 ]. How more frequent sampling would combine with geolocation data is an important future question.…”
Section: Resultssupporting
confidence: 84%
“…The app recorded individuals’ activity levels, geographic movements (described below), light exposure, and social interaction. We also collected physiological data during some parts of the study, as presented by Carr et al [ 19 , 20 ]. More details about the study design are available in our previous work [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we identified desynchronised patterns of heart rate, activity and sleep, in participants with BD and BPD (14) and correspondingly, reported an association between desynchrony and differential mood patterns (22). We also demonstrated that individuals with BPD exhibit rest-activity patterns that are suggestive of phase delayed circadian clock function compared with stable BD and healthy controls (23).…”
Section: Introductionmentioning
confidence: 67%
“…Sleep health might also relate to sleep timing (Carr et al, 2018) or the unequal allocation of sleep throughout the week (Wittmann et al, 2006). It is often suggested that any sleep variability is undesirable.…”
Section: Discussionmentioning
confidence: 99%